The Effect of Organic Matter and Mineral Fertilizers on the Growth, Development, and Yield of Winter Wheat Plants in Irrigated Serozem - Meadow Soil Subjected to Leaching - Boymirzaevich, Bobonorov Bekzod; Махмudоvich, Аbrаlоv Мuzаffаr (American Journal of Biology and Natural Sciences, 2025)
This article shows that as the level of leaching in plain area soils increased as a result of flooding, the amount of humus and nutrients in the soil decreased accordingly. To restore soil fertility, organic and mineral fertilizers were applied to irrigated serozem-meadow soils washed away by floods. The soil properties, as a result of restoring fertility in a short time, are described, indicating the winter wheat crop. As a result, it was determined that in the soil samples taken at the high index after the end of the winter wheat vegetation of the field experimental area, i.e., when zoohumus was applied, the humus content in the 0-30, 30-50 cm layers changed by 0.639-0.822%, mobile phosphorus by 29.3-61.5 mg/kg, and exchangeable potassium by 271-379 mg/kg.